Efektivitas iklan pada televisi vs iklan penargetan ulang sebagai media pengingat di masyarakat - Auvarda, Charissa; Irwansyah (Jurnal Studi Komunikasi, 2022)
Today's business is very advanced, especially in trade. Advertisements can affect many aspects, including the image of the related product and brand. Along with the times, advertising on digital media is also considered to be more effective than mainstream media, such as advertising on television. Social media makes everything easier, including being a media advertising. Advertising on social media is becoming more and more interesting because it appears according to the social media users’ needs, where it seems as if they are being ‘predicted.’ The concept of ‘prediction’ is commonly known as retargeting, assisted by statistical data mining techniques that make it easier to detect and display advertisements on social media according to their target. However, several facts still show that advertisements on television are still the main choice by brands and have the highest advertising spending percentage compared to other advertisements. This quantitative research took primary data through a questionnaire which was then processed using SPSS 23 to compare the effectiveness of advertisements on television and retargeting advertisements with Kruskal Wallis non-parametric test and continued with the EPIC Model analysis. The results of the analysis showed that retargeting ads on social media are more effective as a reminder for the consumer.